Frequency of Celiac Disease Among Children with Type I Diabetes Mellitus - Fatima, Mahin; Farooq, Muhammad Hassaan; Mohammad Irshad; Fatima, Mahnoor; Hussain, Nida; Kifayat, Faryal (Indus Journal of Bioscience Research, 2025)
Background: Celiac disease is common autoimmune problem seen in children having type I diabetes mellitus, but many cases remain undiagnosed due to mild or no symptoms. Objective: To determine frequency of celiac disease among children with type I diabetes mellitus. Study Design: Cross sectional study. Duration and Place of Study: Study was done from 10th July 2024 to 10th January 2025 in department of paediatrics, Lady Reading Hospital Peshawar. Methodology: Total 105 children aged 2–13 years with type I diabetes mellitus were included. Patients were assessed for symptoms of celiac disease and biopsy from duodenum was taken for confirmation. Data was analysed using SPSS version 26. Mean and standard deviation were calculated for numerical variables, while frequencies and percentages for categorical variables. Stratification was done and Chi square test was applied. Results: Mean age was 7.53±3.24 years. Females were 57 (54.3%) and males were 48 (45.7%). Celiac disease was found in 40 (38.1%) children while 65 (61.9%) had no disease. Significant association was seen with socioeconomic status (p<0.001), residence (p<0.001) and family history (p=0.042). No significant association was seen with age (p=0.863), gender (p=0.489), weight (p=0.329) and duration of diabetes (p=0.301). Conclusion: Celiac disease is frequent in children with type I diabetes mellitus and linked with some demographic factors